2011
DOI: 10.1108/08288661111165204
|View full text |Cite
|
Sign up to set email alerts
|

Management of financial market scandals – regulatory and values based approaches

Abstract: Purpose -The paper aims to discuss the management of financial market scandals using two different approaches -regulatory and values-based. Design/methodology/approach -The paper discusses the motivations behind financial scandals to occur and then explains in detail both the approaches. The paper first presents the elements of the regulatory approach. Using the teachings of Bhagavan Sri Sathya Sai Baba, the values-based approach are delineated. The paper also compares the two approaches and identifies their r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Many economists propagate free market approach everywhere but the financial sector because banks have to judge the creditworthiness of firms in the process of loan sanctions. Sivakumar (2011) suggested that for financial system integrity banks have to meet specific recommendations, prerequisite, and financial regulations boundaries. The regulators usually grant an appeal right to banks to maintain fairness in operations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many economists propagate free market approach everywhere but the financial sector because banks have to judge the creditworthiness of firms in the process of loan sanctions. Sivakumar (2011) suggested that for financial system integrity banks have to meet specific recommendations, prerequisite, and financial regulations boundaries. The regulators usually grant an appeal right to banks to maintain fairness in operations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies have examined scandals in the context of corporate scandals (Grebe, 2013), media scandals (Lloyd et al., 2014), celebrity scandals (Hood, 2012; Knittel & Stango, 2014), sports scandals (Connor & Mazanov, 2010; Osborne et al., 2016; Sato et al., 2020), financial market scandals (Sivakumar, 2011), political scandals, scandals related to intellectual and development disabilities (Halladay & Harrington, 2015), real products’ impact on high brand equity brand (Thaler et al., 2018) and from the crisis perspective (Bowen et al., 2018). Though the areas mentioned above have been explored in detail, there are potential gaps in the literature in the context of brand scandal and its impact on consumer attitudes.…”
Section: Introductionmentioning
confidence: 99%